Getting ready for L-day - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
By the time the government of Madagascar put out an appeal for international assistance in July 1997, the most recent invasion of locusts had already wreaked havoc. In the southern half of the country, in the Central Highlands and part of the...